THE EFFECT OF GREEN ACCOUNTING AND ENVIRONMENTAL PERFORMANCE ON COMPANY PROFITABILITY - Ines Dwi Susanti; Lesi Hertati; Andini Utari Putri (Transpublika Publisher, 2023)
This study aims to analyze the effect of green accounting and environmental performance on company profitability (a survey of mining companies listed on the IDX for the 2018-2021 period). This is a quantitative research. Purposive sampling was utilized to choose 12 mining companies trading on the Indonesia Stock Exchange as the data source for this study. Secondary data sources used in this study include information from the annual reports of mining companies traded on the Indonesia Stock Exchange. Descriptive statistics, tests for normality and multicollinearity and heteroscedasticity and autocorrelation, as well as multiple linear regression analysis, followed by the F test, and t tests, were all utilized to analyze the data for this study. The study found that mining companies listed on the Indonesia Stock Exchange benefited financially from Green Accounting and Environmental Performance between 2018 and 2021.